Real-Time ROADM Filtering Penalty Characterization and Generalized Precompensation for Flexible Grid Networks - Jie Pan; Sorin Tibuleac (IEEE Photonics Journal)
Concatenated filtering is an important impairment in high-spectral density transmission systems enabled by flexible-grid reconfigurable optical add-drop multiplexers (ROADMs). In this paper, an analytical model for wavelength selective switches (WSS) modules is used to determine the statistical distribution of experimentally measured filter shapes and to obtain the cascaded filter characteristics. A generalized approach for filtering penalty assessment is proposed and verified using a commercial 200G 16-quadrature amplitude modulation (16QAM) transponder and WSS modules. A practical method for filter penalty reduction is described, whereby a single, optimized digital pre-equalization filter is used to compensate filtering effects of multiple concatenated WSSs. This pre-equalization of cascaded ROADM filters is demonstrated with a 100G quadrature phase shift keying (QPSK) C-form factor pluggable (CFP) transponder operating on the 37.5-GHz grid, resulting in a doubling of the number of WSSs, which can be supported per link from three to six.